2017
DOI: 10.18332/tpc/70087
|View full text |Cite
|
Sign up to set email alerts
|

Process evaluation and challenges of implementation of a school-based waterpipe tobacco smoking prevention program for teens in Lebanon

Abstract: INTRODUCTION Waterpipe tobacco smoking is increasing globally particularly among youth. In Lebanon, the high prevalence of waterpipe tobacco smoking among younger age groups calls for immediate intervention particularly given its negative health effects. To date, such interventions have rarely been implemented or evaluated. METHODS This manuscript describes the process evaluation of a school-based intervention to prevent/delay waterpipe tobacco smoking among 6th and 7th graders (n=844) in Lebanon. Process eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 22 publications
0
6
0
3
Order By: Relevance
“…Environmental factors such as easy and inexpensive access, tobacco flavoring, and the numerous WP lounges in the city make the role of the environment more and more important, which is in line with the previous studies. [183435] Furthermore, the WP lounges in our country are attractive to students, and WP smoking venues represent a gathering place. [3637] Indeed, to change the environment requires intersectional collaboration and general policy at the macro level.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental factors such as easy and inexpensive access, tobacco flavoring, and the numerous WP lounges in the city make the role of the environment more and more important, which is in line with the previous studies. [183435] Furthermore, the WP lounges in our country are attractive to students, and WP smoking venues represent a gathering place. [3637] Indeed, to change the environment requires intersectional collaboration and general policy at the macro level.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a policy prohibiting smoking in schools, many schools allow smoking on their premises. We have described these contextual challenges to this intervention more fully previously [ 52 ]. All the above contextual factors make efforts to effectively message around tobacco prevention and control difficult; and suggest that we may not have found changes in behavior even with a follow-up assessment.…”
Section: Discussionmentioning
confidence: 99%
“…The ten sessions of the intervention were organized as follows: four sessions were knowledge-based, and the other six were skill-based, including: media critical analysis, decision-making skills, refusal skills and social promise. More information on the intervention can be found elsewhere [ 52 ].…”
Section: Methodsmentioning
confidence: 99%
“…The studies resulting from our search were conducted in 17 different LMICs across five geographical regions: Latin America (Brazil [51][52][53][54][55], the Dominican Republic [56], Mexico [57], Surinam [58]), Africa (Malawi [59], South Africa [60][61][62]), the Middle East (Lebanon [63], Syria [64]), Asia (China [65][66][67][68][69], India [49,50,[70][71][72][73][74][75], Indonesia [73,76], Malaysia [77], Nepal [78,79], Pakistan [80], Russia [81], Thailand [82][83]) and Oceania (Fiji [85]) (table 1 and figure 3). Most studies were based in healthcare settings (n=17; primary care (n=9), secondary care (n=5), primary/secondary care combined (n=3)), followed by schools (n=13), and the community (n=6).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The fifth critical factor, "Resource availability", can be particularly challenging to address. One included study reported that workshop facilitators overcame the barrier of transportation costs by ride sharing and delivering several sessions per visit to reduce the number of visits [63]. Reducing the impact of the lack of resources generally requires innovative system strengthening [16].…”
Section: Ensure Compatibilitymentioning
confidence: 99%